Relationship between Neutrophil to Lymphocyte Ratio (NLR) and Lymphocyte to Monocyte Ratio (LMR) with Severity of Ischemic Stroke - Paramadina, Izzati; Kusumaningsih, Dwi; Sulistyani, S; Puspitasari, Metana (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study was to determine the correlation between Neutrophil to Lymphocyte Ratio (NLR) and Lymphocyte to Monocyte Ratio (LMR) with the severity of ischemic stroke. Methodology: According to the criteria, a cross-sectional sample of ischemic stroke patients at Yarsis Islamic Hospital in Surakarta (January 2023–November 2024) participated in this observational analytical study, which used the National Institutes of Health Stroke Scale (NIHSS) as a severity measure. Results: 44 subjects were obtained with an equal ratio of gender and hypertension was the most common comorbidity. A substantial relationship between the NLR with the NIHSS score (p value = 0.001) and between LMR with the NIHSS score (p value < 0.001) was discovered using bivariate analysis. NLR (OR 4.713; p = 0.044) and LMR (OR 10.780; p = 0.043) had a 42.2% (R square = 0.422) impact on the severity of ischemic stroke, according to the findings of the logistic regression test. Applications: Based on this study, there is a significant relationship between NLR and LMR with the severity of ischemic stroke. As a consequence, NLR and LMR test findings may serve as a substitute indicator of acute ischemic stroke patients' severity.